Solve for j 396=6(-8j+2)

Math
396=6(-8j+2)
Rewrite the equation as 6(-8j+2)=396.
6(-8j+2)=396
Divide each term by 6 and simplify.
Tap for more steps…
Divide each term in 6(-8j+2)=396 by 6.
6(-8j+2)6=3966
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6(-8j+2)6=3966
Divide -8j+2 by 1.
-8j+2=3966
-8j+2=3966
Divide 396 by 6.
-8j+2=66
-8j+2=66
Move all terms not containing j to the right side of the equation.
Tap for more steps…
Subtract 2 from both sides of the equation.
-8j=66-2
Subtract 2 from 66.
-8j=64
-8j=64
Divide each term by -8 and simplify.
Tap for more steps…
Divide each term in -8j=64 by -8.
-8j-8=64-8
Cancel the common factor of -8.
Tap for more steps…
Cancel the common factor.
-8j-8=64-8
Divide j by 1.
j=64-8
j=64-8
Divide 64 by -8.
j=-8
j=-8
Solve for j 396=6(-8j+2)

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top